PROYECTO DE FACTIBILIDAD PARA LA CREACION DE UNA EMPRESA DEDICADA A LA PRODUCCION Y COMERCIALIZACIÓN DE LECHUGAS HIDROPONICAS, EN LA CIUDAD DE LOJA - Jumbo Quichimbo, Gabriela Nicole (2016)
Agriculture in Ecuador has gradually grown from the early '90s because the eating habits of the population have positively changed toward greater consumption of vegetables in your daily diet, this represents in the agricultural GDP and 2.97% in national GDP 0.26% on vegetables (excluding potatoes). In this context, this proposal provides for the creation of a production unit of hydroponic lettuce developed with a different alternative called hydroponic cultivation, which is growing plants without using soil, using water as a medium, adding a nutrient solution required by the plant, for normal growth and development. Hence the real need to produce goods and services, being entrepreneurs and facing the grave crisis facing our country, being convenient to make and execute the thesis project entitled: "PROJECT FEASIBILITY FOR THE CREATION OF A COMPANY DEDICATED TO THE PRODUCTION AND MARKETING HYDROPONIC LETTUCE iN THE CITY OF LOJA "the same contributing to the development of this city. A brief presentation was made about the precise content of the thesis project, as well as evidence of the importance of the topic, the contribution and the project structure; a theoretical foundation that synthesized and argument phase of the investment project to achieve the proposed objectives was based on the identification of materials, methods, techniques and procedures that allowed a comprehensive description of the proposal for the implementation of the Company are executed producer and marketer of hydroponic lettuce in the city of Loja. The market study analyzes the supply andthe demand. To all this, a survey was conducted both plaintiffs and bidders, and then determine the unsatisfied demand is 410'138.560 grams for the first year, the installed capacity is 100% and the capacity utilization of the project is 140 determined '940,000 for the first year only. The place for the implementation of the company is in the Barrio "Punzara" Soldier Cape R. Hector Vasquez and Pilco, south of the city of Loja. Administrative and legal study of the company facilitates determining the business group's mission, vision, objectives, constitution, organization and functions manuals. The company will trade under the name "" HYDROPONIC "Cia. Ltda. The objective of the company is to produce and market quality hydroponic lettuce customer delivering a natural and healthy vegetable planted with the necessary 5 nutrients and collaboration of workers to obtain favorable results. Your marketing will be held in the city of Loja. To learn about the project investment (investment in fixed assets, deferred and working capital), investment financing, budget revenues and expenditures, cost analysis, break-even points, study and analysis of financial statements (losses profit and cash flow), the financial economic Study. Finally the project evaluation was performed to establish the suitability of the project and its implementation for which the following indicators such as net present value of $ 573,645.07 was analyzed; Internal rate of return of 211.92%; Benefit Cost Ratio is $ 1.62 for each dollar invested a return of 62 cents will be obtained; Capital recovery period is 5 months and 8 days; Sensitivity analysis indicates that the project supports an increase in the cost of 89.55% for a total of 0.99% and a sensitivity analysis is the decrease in revenues of 41.50%, giving a total of 0.99 %; so the project is feasible, the conclusions and recommendations so determined, accompanied by the bibliographies consulted with their respective annexes.